2015
DOI: 10.1038/nn.3912
|View full text |Cite
|
Sign up to set email alerts
|

Neddylation inhibition impairs spine development, destabilizes synapses and deteriorates cognition

Abstract: Neddylation is a ubiquitylation-like pathway that controls cell cycle and proliferation by covalently conjugating Nedd8 to specific targets. However, its role in neurons, nonreplicating postmitotic cells, remains unexplored. Here we report that Nedd8 conjugation increased during postnatal brain development and is active in mature synapses, where many proteins are neddylated. We show that neddylation controls spine development during neuronal maturation and spine stability in mature neurons. We found that neddy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 73 publications
3
103
0
Order By: Relevance
“…We speculate that the overwhelming neddylation seen in diseased hearts is likely a pathogenic factor contributing to cardiac dysfunction. Neddylation inhibition by NAE1 deficiency in neurons results in loss of synapses, impaired neurotransmission, and cognitive deficits (16). In the future, more in-depth studies are imperative to determine the pathophysiological significance of neddylation in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the overwhelming neddylation seen in diseased hearts is likely a pathogenic factor contributing to cardiac dysfunction. Neddylation inhibition by NAE1 deficiency in neurons results in loss of synapses, impaired neurotransmission, and cognitive deficits (16). In the future, more in-depth studies are imperative to determine the pathophysiological significance of neddylation in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…DEN1 was originally isolated as a NEDD8-specific C-terminal processing enzyme based on its in vitro activity (26). However, NEDD8 processing is not detectably impaired in den1 mutants from fission yeast (Schizosaccharomyces pombe), fungi (Aspergillus nidulans), Arabidopsis, Drosophila, or mice, suggesting that the in vivo activity of DEN1 may be different from its reported in vitro activity, or that other functionally redundant proteases can process NEDD8 in den1 mutants (27)(28)(29)(30)(31). Because den1 mutants from different species accumulate high levels of neddylated substrates of a broad molecular range, it was instead concluded that DEN1 serves in vivo to deconjugate NEDD8 from neddylated substrates (27)(28)(29)(30)(31).…”
mentioning
confidence: 99%
“…For instance, genetic deletion of UBA3, a subunit of NEDD8 E1 NAE, led to embryonic lethality of mice at preimplantation stage [91]. Similarly, knockout of NAE1 (also known as APPBP1, the other subunit of NEDD8 E1) or NEDD8 E2 Ubc12 also caused embryonic lethality [92]. The deneddylase CSN consists of 8 subunits from CSN1 through CSN8.…”
Section: Nedd8mentioning
confidence: 99%
“…It is very challenging to identify the UBL substrates given the low abundance of the modified substrates and the dynamic nature of the modification. Several strategies have been developed to enrich UBL-modified proteins from cell/tissue extracts prior to mass spectrometry analysis: a) expression of epitope-tagged UBL [134]; b) immunoprecipitation with monoclonal UBL antibodies; c) affinity purification with peptides containing UBL-interacting motif; and d) expression of UBL mutant with larger C-terminal overhang, which is distinct from di-glycine motif of Ub/UBL after trypsin digestion [92]. Characterization of UBL-modified proteome regulated by the disease under investigation will help identify new targets for disease prevention and therapeutic intervention.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%